L’accompagnement sous tensions : la médiation des politiques curriculaires par les conseillers pédagogiques - Mathou, Cécile (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
This article deals with the role of educational consultants in the implementation of curricular policies (secondary education) in Quebec. Based on fieldwork conducted in two school boards (11 semidirected interviews), we show that these actors, neglected by research, are not neutral relays of official texts. They carry out mediation work that depends on their beliefs and values but also on strategic and pragmatic adjustments. This mediation aims in particular at mitigating the teachingtothetest effects induced by ministerial evaluations. However, their room for manoeuvre remains limited and the tensions inherent in their support work are exacerbated by the curricular changes of the last decade.